Immunological tolerance: scanning a barren landscape for signs of sustained growth - Petropoulos, H; Davies, T; Fairchild, P (BioInsights, 2020)
The immune system is finely poised to respond to the challenge of infection but occasionally lacks discernment, mounting inappropriate responses to agents that pose no threat, thereby driving pathologies as diverse as autoimmune disease, allergy and allograft rejection. Although our understanding of how immunological tolerance is established and maintained and the circumstances that lead to its failure has improved substantially over the past 20 years, translation of these principles into effective treatments has proven unexpectedly difficult to achieve. Here we explore how the underlying principles of antigen recognition have inspired novel approaches to the induction of tolerance and review progress made in their use to pacify an aggravated immune system. While many challenges undoubtedly remain, for those dedicated to commercialising the opportunities that biologicals and cell therapies have begun to provide, the rewards are likely to be substantial.